IMPROVING THE SENSE OF CIVIC DUTY IN ELEMENTARY SCHOOL STUDENTS BASED ON INTERACTIVE METHODS (Academicia Globe: Inderscience Research, 2022)
Instilling in the minds of primary school students that they are citizens, that they are dependent on the state, that they have duties and responsibilities to their parents and their country. This is to improve the sense of citizenship and duty based on interactive methods.